Principal Management in Improving the Professional Competence of Vocational School Teachers in Cianjur Regency - Yayi Solihah DM; Helmawati Helmawati (CV. Media Digital Publikasi Indonesia, 2026)
Improving education quality is a national priority, yet teacher quality in Indonesia still faces significant challenges. This study aims to analyze the managerial role of school principals in enhancing teachers' professional competence. Using a qualitative approach with a case study method, the research was conducted at two vocational high schools with different challenges: SMK Negeri 1 Agrabinta and SMK Negeri 1 Leles in Cianjur Regency. Data were collected through observation, interviews, and documentation studies. The results show that both school principals successfully and effectively implemented the POAC (Planning, Organizing, Actuating, and Controlling) management cycle. Program planning was based on a real analysis of teacher needs, while organizing was done through clear task delegation and internal collaboration. Implementation was carried out through innovative programs such as In-House Training and the adoption of learning models such as PjBL (Project-Based Learning) and Teaching Factory. Evaluation was conducted systematically, using both data-driven comprehensive and direct-feedback formative approaches. Despite facing classic constraints such as limited time, budget, and varied teacher participation, the principals applied adaptive solutions. These solutions included flexible scheduling, utilizing internal resources (teacher mentors, alumni), and strengthening a culture of sharing. These findings affirm that strong, solution-oriented managerial leadership by school principals is the key to overcoming challenges and significantly improving teacher competence, ultimately contributing to the creation of qualified and competitive graduates.